Lipoxin A4 attenuates MSU-crystal-induced NLRP3 inflammasome activation through suppressing Nrf2 thereby increasing TXNRD2 - Zhou, You; Chen, Yongjun; Zhong, Xiaowu; Xia, Hongtao; Zhao, Mingcai; Zhao, Mengyuan; Xu, Lei; Guo, Xiaolan; You, Chong-Ge (Frontiers in Immunology, 2022)
Gout is a common inflammatory disease worldwide. The activation of NLRP3 inflammasome induced by monosodium urate (MSU) crystals has a critical role in gout and prevention of this pathological process is beneficial for patients. LipoxinA4(LXA4) is an endogenous lipoxygenase-derived eicosanoid mediator with a powerful anti-inflammatory properties. However, it is unexplored whether LXA4 can suppress NLRP3 inflammasome ativation induced by MSU crystals. This study aimed to investigate the protective effect of LXA4 on MSU crystals-induced NLRP3 inflammasome activation, and examine the underlying molecular mechanism. We found that LXA4 inhibited MSU crystals-induced NLRP3 inflammasome activation, IL-1β maturation and pyroptosis. More specifically, LXA4 suppressed the assemble of NLRP3 inflammasome, including oligomerization and speck formation of ASC, and ASC-NLRP3 interaction. Furthermore, LXA4 suppressed oxidative stress, the upstream events for NLRP3 inflammasome activation, as evidenced by that LXA4 ruined total ROS generation, and alleviated NADPH oxidase activation and mitochondrial dysfunction. However, it is surprising that LXA4 depressed the Nrf2 activation-a critical molecule in the antioxidant pathway, and then exerted an inhibitory impact on Klf9 expression, and promotional impact on TXNRD2 expression, two molecule located downstream of Nrf2 in sequence. Knockdown of TXNRD2 turned the LXA4 induced- depression of ROS and NLRP3 inflammasome over. Moreover, LXA4 alleviated joint inflammation and prevented cleaves caspase-1 and matured IL-1β production in gouty arthritis rats. Take together, our findings demonstrate that LXA4 can attenuate MSU crystals-induced NLRP3 inflammasome activation, probably through suppressing Nrf2 activation to increase TXNRD2 expression. This study highlights that LXA4 may serve as an attractive new candidate for the treatment of gout.